2018
DOI: 10.2478/msp-2018-0055
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO-CuO flower-like hetero-nanostructures as volatile organic compounds (VOCs) sensor at room temperature

Abstract: ZnO-CuO flower-like hetero-nanostructures were successfully prepared by combining hydrothermal and dip coating methods. Flower-like hetero-nanostructures of ZnO-CuO were examined by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and UV-Vis. The sensing properties of ZnO-CuO flower-like hetero-nanostructures to volatile organic compounds (VOCs) were evaluated in a chamber containing acetone or isopropanol gas at room temperature. The sensitivity of ZnO-CuO flower-like hetero-nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It was reported that low transmittance, i.e. below 380 nm, indicates strong absorbance for ZnO-CuO nanocomposite [18].…”
Section: Uv-visible Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that low transmittance, i.e. below 380 nm, indicates strong absorbance for ZnO-CuO nanocomposite [18].…”
Section: Uv-visible Analysismentioning
confidence: 99%
“…The analysis at various resolutions showed that is the composite is nanoporous and has an irregular shape (Figure 3). However, the morphological structure of ZnO-CuO observed involve nanowire, nanorod, flower-like, spherinoid, nanoflakes, and networked flakes by Zhu et al [24], Jung et al [25], Sabry et al [18], Sakib et al [19], Saravanakkumar et al [21] and Allaf and Hope-Weeks [23], respectively.…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%